The Influence of English Songs on Listening Comprehension of the English Department Students at University - HS, Fatimatu Khoirunnisa; Nada, Azzhura Rizqia; Fatmasari, Nita (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study discussed the influence of using English songs on the listening comprehension of English department students at Universitas Tidar. It used a quantitative research design and collected data through an online questionnaire containing 10 statements rated on a Likert scale. The questionnaire was completed by 30 students, and the data was analyzed using measures of central tendency (mean, mode, median) and measures of variability (standard deviation). The results showed that most students had a positive attitude towards using English songs and found them easy to access and play. There was some variation in the responses, with a higher standard deviation in some statements, which may suggest that not all students had the same level of enthusiasm or agreement about the usefulness of English songs. Overall, the results indicated that English songs could be a valuable tool for improving listening comprehension and creating a more relaxed learning atmosphere for the students at Universitas Tidar.